2020
DOI: 10.1136/rmdopen-2019-000989
|View full text |Cite
|
Sign up to set email alerts
|

Type I IFN system activation in newborns exposed to Ro/SSA and La/SSB autoantibodies in utero

Abstract: ObjectiveIn utero exposure of the fetus to Ro/La autoantibodies may lead to congenital heart block (CHB). In the mother, these autoantibodies are associated with activation of the type I interferon (IFN)-system. As maternal autoantibodies are transferred to the fetus during pregnancy, we investigated whether the type I IFN-system is activated also in newborns of anti-Ro/La positive mothers, and whether fetal IFN activation is affected by maternal immunomodulatory treatment.MethodsBlood drawn at birth from anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 37 publications
0
18
0
Order By: Relevance
“…IFN‐α was analysed in culture supernatants by a dissociation‐enhanced lanthanide fluoroimmunoassay (DELFIA) as previously described 34,35 . The DELFIA assay does not detect the IFN‐α subtype 2b which was used for priming.…”
Section: Methodsmentioning
confidence: 99%
“…IFN‐α was analysed in culture supernatants by a dissociation‐enhanced lanthanide fluoroimmunoassay (DELFIA) as previously described 34,35 . The DELFIA assay does not detect the IFN‐α subtype 2b which was used for priming.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, data from in vitro studies show that anti-Ro–associated single-stranded RNA binds to macrophage Toll-like receptors (TLR) and thus triggers the aforementioned inflammatory and fibrosis cascade [ 46 ]. An important role seems to be played in this context by interferon (IFN), with highly expressed type I IFN response genes [ 46 , 47 ].…”
Section: Pregnancy In Women With Anti-ro/ssa Antibodiesmentioning
confidence: 99%
“…[54][55][56][57] Of note, the same study found that the levels of IP-10 (CXCL10), a protein induced by both type I and type II IFNs and also correlating with disease activity in SLE, 55 did not differ between CHB mothers and mothers of unaffected children. 53 Since this initial study, activation of the type I IFN system and increased expression of SIGLEC-1 have been reported both in cord blood mononuclear cells (CBMCs) from neonates of anti-Ro/La antibody-positive mothers 58 and in heart tissues from foetuses dying with autoimmune CHB. 59 Upregulation of IFN-stimulated genes (ISGs) was observed not only in leukocytes isolated from a CHB foetal heart compared with cells isolated from healthy, electively terminated foetal hearts, 59 but also in other cardiac-derived cell types, albeit to varying degrees.…”
Section: Autoimmune Chbmentioning
confidence: 99%
“…CBMCs derived from newborns in pregnancies both with and without anti-Ro/La autoantibodies have indeed the capacity to produce IFNα following exposure to plasma containing anti-Ro/La antibodies. 58 As maternal antibodies start crossing the placenta around the 6-7th weeks of pregnancy, with 10% of maternal IgG concentrations transferred to the foetus by gestational weeks 17-22, 68 anti-Ro/La autoantibodies, in complex with apoptotic/necrotic material from cardiac cells dying during normal foetal heart remodelling, may activate foetal cardiac immune cells to produce type I IFN.…”
Section: Autoimmune Chbmentioning
confidence: 99%
See 1 more Smart Citation